CRISPR/Cas9-Based Deletion of SpvB Gene From Salmonella gallinarum Leads to Loss of Virulence in Chicken - Basit, Abdul; Tahir, Hamza; Haider, Zulquernain; Tariq, Hafsa; Ullah, Asim; Rehman, Shafiq Ur (Frontiers in Bioengineering and Biotechnology, 2022)
Salmonella Gallinarum causes fowl typhoid in poultry leading to a huge economic loss to the poultry industry. The large virulence plasmid of S. gallinarum has been associated with various systemic infections in poultry. A five-gene spanning region (spvRABCD) of 7.8 kb on the large plasmid mainly confers virulence to the bacteria. However, the exact role of these genes in virulence has not been elucidated yet. SpvB exhibits delayed cell death by preventing actin polymerization followed by apoptosis during intracellular infection. The specific role of SpvB in causing the disease is not known yet. In the current study, the SpvB gene was deleted through CRISPR/Cas9 method from a large virulent plasmid of locally isolated S. gallinarum strain (SG18). The homology-directed repair method was used for complete deletion of SpvB gene using the modified pCas9 plasmid. The SpvB-deleted S. gallinarum strain (ΔSpvB_SG18), when tested for its virulence in broiler chicken showed no diseases signs and mortality. In addition, the avirulent strain does not affect the bird’s weight and was rapidly cleared from the liver after infection. However, it cleared from the intestine only after 4–5 days, which suggests that the ΔSpvB_SG18 strain is unable to invade from the intestine to the liver. This is the first study to report a complete gene deletion from the S. gallinarum virulent plasmid and its effect. This method will be useful for the deletion of virulent genes from S. gallinarum, to study their role in pathogenesis, and to prepare an effective vaccine strain for controlling fowl typhoid in poultry.